KORELASI ANTARA TINGKAT KECEMASAN DENGAN FUNGSI KOGNISI (Studi deskriptif pada siswa yang mengikuti ekstrakurikuler futsal di Sma Pasundan 8 Bandung) - Muhammad Fahmi Ayatulloh, - (2021)
Anxiety is an emotion in a person that is temporary when facing various problems. Anxiety often occurs during futsal games, when students are filled with anxiety in themselves, concentration and focus will be reduced, thus disrupting the development of cognitive function. This study aims to find out the relationship between anxiety and cognition function in students who perform futsal extracurricular activities. The method used is Descriptive Study with quantitative approach. The population in this study is extracurricular futsal members of SMA Pasundan 8 Bandung numbering 19 people. The data collection technique uses TMAS questionnaires to measure anxiety in samples, and Concentration Grid Exercise, Digit SPAN, and TPA (Academic Potential Test) tests to measure cognition function in samples. The results of the study were analyzed using pearson correlation test on SPSS version 25 statedthe results of the calculation. Hypothetical test obtained p = 0.002<0.05. That is, there is a significant association between anxiety to cognition function in futsal playing skills. Keywords: Anxiety, Cognition Function, Futsal